2020
DOI: 10.1002/jemt.23530
|View full text |Cite
|
Sign up to set email alerts
|

Retinal characterization in the eyes of two bats endemic in the Egyptian fauna, the Egyptian fruit bat (Rousettus aegyptiacus) and insectivorous bat (Pipistrellus kuhlii), using the light microscope and transmission electron microscope

Abstract: Bats are the only mammals that can fly in the dark without eye usage. This study was conducted to describe the structural and functional adaptations of the retina of two bats very common in the Egyptian fauna having a different lifestyle: the Egyptian fruit bat (Rousettus aegyptiacus) and insectivorous bat (Pipistrellus kuhlii). Seven eyes were collected from adult individuals of each species. Examination of the retina using a light microscope and a transmission electron microscope was carried out. The retina … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 78 publications
(107 reference statements)
1
10
0
Order By: Relevance
“…The unusual choroidal and retinal morphology observed in this study for Eidolon helvum have since been reported for other megachiropteran, and in particular, pteropodid bats 10,29,30 . The role of the choroidal papillae in blood supply to retinal tissues has been well documented 31,32 but their role in vision has been a matter of controversy among scientists with some scientists asserting that the presence of the choroidal papillae led to improved visual sensitivity through an increase in the photosensitive area and number of photoreceptors 32,33 .…”
Section: Choroidoretinal Undulationssupporting
confidence: 80%
See 1 more Smart Citation
“…The unusual choroidal and retinal morphology observed in this study for Eidolon helvum have since been reported for other megachiropteran, and in particular, pteropodid bats 10,29,30 . The role of the choroidal papillae in blood supply to retinal tissues has been well documented 31,32 but their role in vision has been a matter of controversy among scientists with some scientists asserting that the presence of the choroidal papillae led to improved visual sensitivity through an increase in the photosensitive area and number of photoreceptors 32,33 .…”
Section: Choroidoretinal Undulationssupporting
confidence: 80%
“…This perception is required for the survival of the organism especially during its periods of peak activity. The activity pattern of an animal is therefore related to its ocular morphological characteristics and has been reported by many ocular scientists [1][2][3][4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 95%
“…Following the fixation, the samples were fixed at 1% osmium tetroxide (OsO 4 ), then dehydrated in a graded dilution of absolute ethanol (Aboelnour, Noreldin, Massoud, & Abumandour, 2020; Kandyel et al, 2021). After that, samples were embedded in epoxy resin.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the inner side of the epithelial layer of the retina was appeared as a layer wrapped around itself (Figure 5b, c). The vertebrate visual system had a species-specific adaptation either in aquatic, semi-aquatic, or terrestrial conditions, in close relation to the morphological structure of the eye (Aboelnour et al, 2020;Jones et al, 2007;Katzir & Howland, 2003;Onuk et al, 2021). Several previously published articles were deeply discussed the mechanisms by which environmental factors can influence the adaptation of the aquatic eye and the visual quality such as temperature and subaquatic pressure, aquatic turbidity, and chromatic absorption of light, in addition to, other climatic changes.…”
Section: Scanning Electron Microscopic Observationsmentioning
confidence: 99%
“…The optical system of the teleost fish is considered of utmost importance, because it is involved in numerous pivotal activities of the fish lifestyle such as: migration, reproduction, food search, or swimming (De Busserolles et al, 2013; El‐Bakary & Abumandour, 2017a; Onuk et al, 2021; Schmitz & Wainwright, 2011b). Moreover, the visual adaptation provides good information on the ecological diversity of the Vertebrate World (Aboelnour et al, 2020; Akat & Arikan, 2013; Litherland et al, 2009).…”
Section: Introductionmentioning
confidence: 99%